Targeted Metabolomics With Ultraperformance Liquid Chromatography–Mass Spectrometry (UPLC-MS) Highlights Metabolic Differences in Healthy and Atopic Staffordshire Bull Terriers Fed Two Different Diets, A Pilot Study - Moore, Robin; Anturaniemi, Johanna; Velagapudi, Vidya; Nandania, Jatin; Barrouin-Melo, Stella Maria; Hielm-Björkman, Anna (Frontiers in Veterinary Science, 2020)
Background: While anecdotal evidence has long claimed that a raw meat-based diet (RMBD) improves the metabolic health of canines, no rigorous scientific study has clarified this issue. Canine atopic dermatitis (CAD) has also been linked to metabolic health, but its relation to diet remains poorly understood. This study investigates whether dietary choice is linked to metabolic health in healthy and CAD-diagnosed canines via targeted serum and urine metabolomic analysis of polar, non-ionic metabolites, as well as whether the underlying CAD-condition modulates the response to nutritional intake. Material and methods: Serum metabolites of client-owned Staffordshire Bull Terriers, divided into CAD-diagnosed (n=14) and healthy (n=6) cohorts, were studied. Urine metabolites of a subset of the CAD-diagnosed canines (n=8) were also studied. The canines were split into two cohorts based on diet. The first cohort were fed a commercially available high-fat, moderate-protein, low-carbohydrate RMBD (n=11, CAD diagnosed n=8, healthy n=3). The second cohort were fed a commercially available moderate-fat, moderate-protein, high-carbohydrate kibble diet (KD) (n=9, CAD diagnosed n=6, healthy n=3). The diet intervention period lasted approximately 4.5 months (median 135d). Statistical analysis of the serum profiles across all dogs (n=20) and the urine profiles of the CAD-diagnosed subset (n=8) were performed. Results and discussion: The KD cohort was found to have higher concentrations of methionine than the RMBD cohort, both in serum (all dogs, p<0.0001) and in urine (CAD-only cohort, p<0.0002), as well as cystathionine and 4-pyridoxic acid. Methionine plays important roles in homocysteine metabolism, and elevated levels have been implicated in various pathologies. The CAD (n=14) cohort dogs showed starker metabolic changes in response to diet regarding these pathways compared to the healthy (n=6) cohort. However, there was no significant change in CAD severity as a result of either diet. Likely due to the higher meat content of the RMBD, higher concentrations of several carnitines and creatine were found in the RMBD cohort. Citrulline was found in higher concentrations in the KD cohort. Our findings provide insight into the relationship between diet and the serum and urine metabolite profiles of canines. They also suggest that neither diet significantly affected CAD severity.